Taxonomy and Ecology of Sympatric Ampelisca Species (Crustacea, Amphipoda) From the Strait of Gibraltar to the Strait of Dover, North-Eastern Atlantic - Dauvin, Jean-Claude; Sampaio, Leandro; Rodrigues, Ana Maria; Quintino, Victor (Frontiers in Marine Science, 2021)
The Ampeliscidae Kröyer, 1842 is amongst the most diverse amphipod families; it comprises four genera, Ampelisca being the richest with more than 200 species. The Ampelisca genus presents high morphological homogeneity and the identification of the species by ecologists remains difficult. Ampelisca are also characterized by a high degree of sympatry, a rare situation in amphipods, and in this study we report up to nine species coexisting at the same site. Recent benthic sampling and publications, namely on the Portuguese continental shelf and the English Channel, permit to revisit the available data on the taxonomy and propose an updated species identification key, as well as the distribution and ecology of the 40-recorded Ampelisca species along the North Eastern Atlantic coast, from the Strait of Gibraltar, in the South, to the Strait of Dover, in the North. The data allow discussing on the sympatry and syntopy of such diverse amphipod family with the co-occurrence of several species at various scales of observations, from the wider regional area, to the narrower local habitat. Two Ampelisca species were recorded exclusively on hard bottom, while the other tend to inhabit specific types of soft bottom, ranging from deep mud to shallow coarse sand and gravel, with a preference for continental shelf muddy and sandy habitats. A future sea water temperature increase scenario could modify the species geographical distribution and reproductive cycle, in this temperate North-eastern Atlantic province.